Analysis by region of outcomes for patients with advanced renal cell carcinoma treated with cabozantinib or everolimus: a sub-analysis of the METEOR study. (2nd January 2022) - Schmidinger, Manuela; Motzer, Robert J.; Rolland, Frederic; Staehler, Michael; Rink, Michael; Retz, Margitta; Csoszi, Tibor; McCaffrey, John A.; De Giorgi, Ugo; Caserta, Claudia; Duran, Ignacio; Benzaghou, Fawzi; et al.
Abstract: Introduction: METEOR was a phase 3 trial (NCT01865747) of cabozantinib versus everolimus in adults with advanced or metastatic clear cell RCC previously treated with VEGF receptor (VEGFR) tyrosine kinase inhibitors (TKIs). This post hoc analysis of METEOR compared outcomes for patients recruited from European and non-European countries. Material and methods: Adults with advanced/metastatic clear cell RCC who had received ≥ 1 prior VEGFR-TKI treatment were randomized 1:1 to receive cabozantinib or everolimus. Patients were categorized by recruitment region: Europe or outside of Europe (rest of world [RoW]). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and adverse events (AEs) were compared between regional subgroups. Results: In total, there were 320 eligible patients from Europe (cabozantinib, 167; everolimus, 153) and 338 from RoW (North America, 240 patients; Asia-Pacific, 86; Latin America, 12; randomized as cabozantinib, 163; everolimus, 175). PFS and OS were longer with cabozantinib than with everolimus and similar for the Europe and RoW subgroups. For PFS, the hazard ratio (HR) for cabozantinib versus everolimus was 0.54 for the Europe subgroup ( p < .001) and 0.50 for the RoW subgroup ( p < .001). For OS, the HR was 0.75 for the Europe subgroup ( p = .034) and 0.69 for the RoW subgroup ( p = .006). ORR in the Europe subgroup was 15% for cabozantinib and 3.9% for everolimus ( p < .001). For the RoW subgroup, ORR was 20% for cabozantinib and 2.9% for everolimus ( p < .001). Incidence of grade 3/4 AEs were similar for the Europe (cabozantinib, 74%; everolimus, 58%) and RoW subgroups (cabozantinib, 69%; everolimus, 64%). Conclusion: In the METEOR trial, efficacy outcomes for patients recruited from European and non-European countries favored cabozantinib over everolimus. The efficacy and safety results for the regional subgroups were consistent with those of the overall METEOR population.